Analysis of the Influence of Facilities and Infrastructure, Adoption of IT and Principal Leadership on Teacher Performance - Mohzana; Fatimah Malini Lubis; Akhmad Ramli; Imam Jayanto; Djunaedi Djunaedi; Mozart Malik Ibrahim (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the influence of facilities and infrastructure, adoption of information technology, and principal leadership on teacher performance. This study was conducted in a public high school involving 150 teachers as respondents. The research method used was quantitative with a survey approach. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that facilities and infrastructure positively and significantly affected teacher performance. Likewise, adopting information technology is important in improving the efficiency of teaching, planning, and assessment. Principal leadership also significantly affected teacher motivation, discipline, and professional development. The combined effect of the three variables showed a strong and positive correlation to improving teacher performance. Furthermore, this study highlights the need for a systemic approach in school management. Facilities and infrastructure are physical and psychological supporting elements affecting teacher comfort and work enthusiasm. Adopting information technology must be accompanied by ongoing training so that teachers are not only passive users but can also explore the innovative teaching potential. Meanwhile, the principal needs to play a role as a transformational leader who not only directs but also inspires teachers to continue to develop. These findings can be used as a reference for school management and policymakers in designing effective strategies to support and improve the quality of education.